VALIDATION OF WORDWALL ASSESSMENT INSTRUMENTS BASED ON STORIES WITH SERIES OF PICTURES - Suhartinah Suhartinah; Erna Budiarti; Nata Priatna; Susi Mulyawati; Aisyah Aisyah; Ayu Dwi Widia (International Conferences on Early Childhood Education Proceedings, 2024)
Abstract Picture story-based Wordwall assessment is an assessment method that utilizes the Wordwall digital platform to measure students' understanding and engagement with series of picture stories. Serial picture stories are used as an interactive learning medium, and through this assessment, the main goal is to evaluate the extent to which students can understand the content of the story, identify relationships between parts of the story, and respond appropriately to the questions or tasks asked. This research aims to validate the assessment instrument developed using the Wordwall platform based on a series of illustrated stories. This instrument is designed to measure students' ability to understand and interact with learning material through the use of serial picture stories in an educational environment. The research method uses a quantitative and qualitative approach involving student participation as test subjects. Validation is carried out through content analysis, internal consistency analysis, as well as validity and reliability tests. The research results show that the assessment instrument developed through the Wordwall platform has good validity. The validation process involved content analysis and empirical trials with student participation, which consistently showed that this instrument was able to accurately measure students' understanding and interaction with serial illustrated stories. In addition, the level of reliability of the instrument that consistently measures the abilities being measured provides confidence that the assessment results can be reliable and consistent in describing students' abilities.